2022
DOI: 10.7717/peerj.13482
|View full text |Cite
|
Sign up to set email alerts
|

Application of hydrophilic polymers for the preparation of tadalafil solid dispersions: micromeritics properties, release and erectile dysfunction studies in male rats

Abstract: The objective of the present study was to improve the dissolution rate and aphrodisiac activity of tadalafil by using hydrophilic polymers. Solid dispersions were prepared by solvent evaporation-Rota evaporator using Koliphore 188, Kollidon® VA64, and Kollidon® 30 polymers in a 1:1 ratio. Prepared tadalafil-solid dispersions (SDs) evaluated for yield, drug content, micromeritics properties, physicochemical characterizations, and aphrodisiac activity assessment. The optimized SDs TK188 showed size (2.175 ± 0.24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Similarity index results of the dissolution profiles of a 3D printlet (APN2) before and after undergoing stability testing (Figure 12). The results indicate an f2 value of approximately 70.59, which is a measure of the similarity between the two dissolution profiles [44,45].…”
Section: Stability Studiesmentioning
confidence: 90%
“…Similarity index results of the dissolution profiles of a 3D printlet (APN2) before and after undergoing stability testing (Figure 12). The results indicate an f2 value of approximately 70.59, which is a measure of the similarity between the two dissolution profiles [44,45].…”
Section: Stability Studiesmentioning
confidence: 90%
“…The resulting powder consists of drug-polymer particles in a solid state called spray dried solid dispersions (SDSDs) [35]. MM Ahmed et al reported the improved dissolution and aphrodisiac activity of sildenafil and tadalafil SDSDs using glycyrrhizin [36], [37], [31]. Spray-dried amorphous solid dispersion of diosmin in soluplus was prepared by MK Anwer and reported to show improved hepato-renoprotective and anti-oxidant properties [38].…”
Section: Of 21mentioning
confidence: 99%
“…Pharma test automated powder flow analyzer was used (PTG-S4 Hainburg Germany) to measure the angle of repose (𝞱𝞱). The 𝞱𝞱 is an angle between the surface of the pile and the horizontal plane [37]. 𝞱𝞱 = 𝑪𝑪𝑪𝑪𝒊𝒊 −𝟏𝟏 𝒘𝒘 𝑷𝑷 ⁄…”
Section: Angle Of Reposementioning
confidence: 99%
“…Aldawsari et al have prepared solid dispersions of sildenafil using hydrophilic polymers such as Kollidon® 30, Kolliphor® P188, and Kollidon and demonstrated enhanced dissolution rate, and significant improvement in inter-copulatory efficiency and copulatory efficiency in male rat models ( Aldawsari et al, 2021 ). A previous study also explored the spray drying technology to prepare amorphous solid dispersion of tadalafil, another PDE5 completive inhibitor, using Kollidon® VA64, Koliphore 188, and Kollidon® 30 polymers to improve the ED ( Ahmed et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%